Alpha-Catulin, a New Player in a Rho Dependent Apical Constriction That Contributes to the Mouse Neural Tube Closure - Karpińska, Kamila; Cao, Christine; Yamamoto, Vicky; Gielata, Mateusz; Kobielak, Agnieszka (Frontiers in Cell and Developmental Biology, 2020)
Coordination of actomyosin contraction and cell-cell junctions across a field of cells, generates forces that can lead to tissue morphogenetic processes like the formation of neural tube (NT), however, its molecular mechanisms responsible for regulating and coupling this contractile network to cadherin adhesion remain to be fully elucidated. Here, using the gene trap we unveil the new player in this process, α-catulin, that shares sequence homology with vinculin and α-catenin. Ablation of α-catulin in mouse causes defective NT closure, due to impairment of apical constriction, concomitant with apical actin and P-Mlc2 accumulation. Using the 3D model we showed that α-catulin localizes to the apical membrane and its removal alters the distribution of active RhoA and polarization. Actin cytoskeleton and P-Mlc2, downstream target of RhoA, are not properly organized, with limited accumulation at the junctions, indicating lack of junctions stabilization. Our data suggest that α-catulin plays an important role during NT closure by acting as a scaffold for RhoA distribution, resulting in proper spatial activation of myosin to influence actin-myosin dynamics and tension at cell-cell adhesion.